Molecular Characterization and Identification of Aflatoxigenic Fungi Associated with Poultry Feed in Port Harcourt, Rivers State - Thankyou Saturday Okpabi, Ngozi O. Izuchukwu (American Journal of Bioscience and Clinical Integrity, 2026)
The contamination of livestock feeds by aflatoxigenic fungi poses significant health and economic risks, affecting both animal productivity and human food safety. This study investigated the occurrence, molecular characterization, and aflatoxigenic potential of fungal contaminants in commercial poultry feeds obtained from Rumuolumeni, Mile III, and Choba in Port Harcourt, Rivers State. About nine feed samples (starter, grower, and finisher) were aseptically collected and analyzed using standard microbiological methods. Ten grams of each sample were serially diluted and inoculated on Potato Dextrose Agar (PDA) supplemented with chloramphenicol to isolate fungal species. Distinct colonies were purified and identified based on morphology and molecular characteristics. DNA was extracted using the CTAB method, and the Internal Transcribed Spacer (ITS) region was amplified with ITS1/ITS4 primers. The resulting PCR products were sequenced, analyzed via BLAST on the NCBI database, and phylogenetically compared using MEGA 11 software. Aflatoxin production was confirmed through culture on YES agar, methanol extraction, immunoaffinity purification, and High-Performance Liquid Chromatography (HPLC) quantification. Results revealed that all feed samples were contaminated with fungi, with Aspergillus flavus, A. niger, A. fumigatus, Penicillium, Fusarium, and Rhizopus species identified. Molecular analysis confirmed A. flavus as the predominant aflatoxigenic fungus, clustering with known aflatoxin-producing lineages (bootstrap 85–92%). HPLC analysis showed that A. flavus isolates produced Aflatoxins B₁, B₂, G₁, and G₂, with B₁ being the most dominant and toxic (45.6–60.2 µg/kg). It is concluded that poultry feeds in the study area are significantly contaminated with aflatoxigenic A. flavus, posing serious food and feed safety concerns. The study recommends strict quality control during feed production, proper storage conditions, and routine screening for aflatoxins to safeguard animal and public health.